Urgensi Rihlah Ilmiah Ahli Hadis - Hidayat, Andi Muhamad; Kosasih, Engkos; Mighwar, Muhammad Al; Rafiq, Muhamad Chaedar (TSAQOFAH, 2024)
This article discusses the extensive academic practices of Hadith scholars. They undertook journeys to seek authentic or sahih Hadiths. The primary aim of this research is to safeguard the authenticity and originality of the Prophet's Hadiths. The method used is descriptive analysis, which explains the urgency of these scholarly activities. The scholarly tradition of Hadith search began during the time of Prophet Muhammad (PBUH), continued by his companions and the Tabi'in, and subsequent generations. Al-Baghdadi explains that their journeys had two main objectives: first, to ensure the highest sanad (chain of narration) and to hear directly from the Prophet (PBUH) himself; second, to meet, discuss, and learn from Hadith experts (huffâzh). Thus, this article provides a detailed description of how Hadith scholars from various generations made significant efforts to preserve the authenticity of Hadith, using descriptive analysis to illustrate the urgency of their scholarly activities in the ritual tradition of Hadith search.